ANALISIS BEBERAPA SIFAT FISIKA TANAH PADA LAHAN SAWAH DI KELURAHAN ANJUNGAN MELANCAR - Agustine, Leony (Jurnal Agriovet, 2024)
The physical properties of soil are environmental factors that greatly influence the amount of water and air in the soil and indirectly influence the amount of nutrients in plants. The agricultural sector of the Anjunga Melancar community has quite large potential, one of which is rice cultivation, unfortunately in this case there are still obstacles in the community, namely that good and appropriate land management methods have not been found. There are several ways to manage rice fields so that they can produce rice effectively, one of which is by knowing the physical properties of the soil. The method used for this research is a Free Grid Survey method at a detailed survey level with a map scale of 1:10,000. Observation points are determined using a physiographic system which is based on land map units obtained from the overlay of administrative maps, land use maps, soil type maps and also slope class maps. The area of land studied was 60 hectares and consisted of 4 land units. The results of the assessment of the physical properties of the soil at the research location are seen from the suitability of the land as follows: Land Unit 1 rooting media (thickness of peat) is the limiting factor, Land Unit 2 is the limiting factor for rooting media (thickness and maturity of peat), Land Unit 3 rooting media (peat maturity). The color of the soil in each Land Unit is dominated by brown to dark brown.